Certain investigation on RC aircraft engine to identify the suitability of Methanol and Castor oil Alternative fuel. Issue 1 (November 2021) - Yuvaraj, S; Thomas Renald, C J; Senthil Kumar, A P; Sadesh, K; Naveen Promoth, D
Abstract: In the current age drones are broadly utilized for different applications in pretty much every field. Because of the disturbing expense of the glow fuel utilized in the RC motors, utilization of the equivalent includes a ton of capital. Adding to it, the current fuel brings about intermittent combustion is in demand of alternate fuel. This paper manages the investigation of existing fuel synthesis and discovering the cost required to dispose of the high capital included, so that considerably more tests and study utilizing the RC Engines 2.5 cc can be completed easily. Methanol and Castor oil Combination is considered as an alternate fuel. The approach includes testing of the fuel to decipher the substance parts and their individual pieces through a progression of tests. Followed by the study of possible additives to enhance the performance of the engine without actually altering the timing intervals. The new creation of the fuel showed up is blended in with extraordinary hardware and the equivalent is tried for essential fuel properties viz., Density, Flash point, Fire point, Calorific value, and so forth The productivity arrangement is made utilizing a pulley instrument and the equivalent is tried for both the energizes. Performance of the R/C aircraft engine was tested with existing glow fuel and the new blend. Results are compared and concluded that the designed blend is a potent alternate fuel for R/C aircraft engines. *Future scope: It can be further tested for its SFC and emission standards. The outcome shows that the new fuel is exceptionally cost productive and the essential substance properties are profoundly improved.